2016
DOI: 10.1210/jc.2015-3803
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Expression of Estrogen Receptors and the Androgen Receptor in Women With Polycystic Ovary Syndrome: A Lifestyle Intervention Study

Abstract: Lifestyle intervention alters, but does not fully restore, ER and AR expression in proliferative and secretory endometrium of obese women with PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 29 publications
0
11
1
6
Order By: Relevance
“…38,39 Recently, it has been shown that the level of ERa and ERa/ERb were decreased in proliferative endometrium, whereas the level of androgen receptor was increased. 40 Therefore, the thin uterine lining in PCOS may result from changes in steroid hormones and receptors. Tamoxifen improves EMT and pregnancy outcomes in PCOS mainly through the ER pathway.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Recently, it has been shown that the level of ERa and ERa/ERb were decreased in proliferative endometrium, whereas the level of androgen receptor was increased. 40 Therefore, the thin uterine lining in PCOS may result from changes in steroid hormones and receptors. Tamoxifen improves EMT and pregnancy outcomes in PCOS mainly through the ER pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, female ERα -/- but not ERβ -/- mice develop obesity and insulin resistance (2). Hulchiy et al (62) have reported that endometrial ERα but not ERβ mRNA is decreased in overweight/obese patients with PCOS compared with controls, which is in contrast to the increased endometrial ERα and ERβ mRNA and/or protein expression observed in patients with hyperandrogenic PCOS (18,19). Thus, it remains unclear how insulin resistance and hyperandrogenism differentially affect ER subtype-mediated regulation of glycolysis in the endometrium in patients with PCOS.…”
Section: Resultsmentioning
confidence: 96%
“…While these reports may suggest a role of abnormal FoxO1 signaling in the development of restricted progesterone-dependent uterine receptivity and decidualization in PCOS, further molecular studies into the mechanistic association between the endometrial PGR and other transcriptional mediators of endometrial receptivity, particularly the Indian hedgehog (IHH) signaling pathway, are warranted. Notably, the fact that the persistence of the abovementioned endometrial irregularities despite adequate metabolic control, lifestyle interventions and the restoration of regular ovulatory cycles [47,69] underpins the need to further examine the link between chronic inflammation and related immunological abnormalities in the development of P4 resistivity in PCOS.…”
Section: Evidence Of Endometrial Progesterone Resistance In Pcosmentioning
confidence: 99%